Phonosurgery: A review of current methodologies. Issue 4 (1st October 2021) - Ulmschneider, Christopher; Baker, Jeffrey; Vize, Ian; Jiang, Jack
Abstract : Cold‐steel has served as the gold standard modality of phonosurgery for most of its history. Surgical laser technology has revolutionized this field with its wide use of applications. Additional modalities have also been introduced such as coagulative lasers, photodynamic therapy, and cryotherapy. This review will compare the surgical modalities of cold steel, surgical lasers, phototherapy and cryotherapy. The mechanism of action, tissue effects and typical uses will be addressed for each modality.